Jamal is comparing his transportation options for an upcoming trip. He’s considering a rental car and a taxi service. Based on his planned routes during his trip, he expects a taxi service would cost about $128. Jamal could also get a rental car for a daily rate and unlimited miles. If Jamal’s trip will last 4 days and he expects to pay about $24 for gas, which graph shows the range of car rental rates that would be cheaper than the taxi service?
Jamal is comparing his transportation options for an upcoming trip. - 1

Answers

Answer 1
Answer:

Answer:

Graph A

Step-by-step explanation:

Say that the car rental rate stands for c dollars ( $ ). We know that Jamal's trip lasts for 4 days, paying $ 24 in expenses for gas, and $ 128 for taxi services. Based on these requirements for his trip the question asks for a graph that models this situation, but lets start with the inequality.

______

The big key here is the part " which graph shows the range of car rental rates that would be cheaper than the taxi service. " Our inequality must thus have the variable " c " on the same side as the payment for gas ($ 24 ), and must be less than the taxi service ( $ 128 ), or in other words a less than sign. Another point is the car rental rate. We know it stands for c, but it is dependent on the number of days. Hence we can conclude the following inequality,

24 + 4c < 128 - Subtract 24 from either side,

4c < 104 - Divide by 4 on either side, isolating c,

c < 26

The range of car rental rates that would be cheaper than the taxi service should be { c | 0 ≤ c < 26 }, knowing variable c stands for the car rental rates.

______

The graph that models this range should be the first one, option A. This graph is not accurate however, as it extends infinitely in the negative direction, and you can't have negative money, or rather be in debt - in this situation.

Answer 2
Answer:

Answer:

A is the answer

Step-by-step explanation:


Related Questions

Rewrite 4+8lnx=2 without logarithms
Write this fraction in the simplest form 15/25
30 points!!! Help me on 1. 2. 3.
HELP PLEASE NEED HELP ASAP
-(- 3.8a - 9b + 5.8)​

A family buys 8 tickets to a show. They also pay a $5parking fee. They spend $61 to see the show.
What is the solution to the story?

13.80
10.60
07.00
8.25

Answers

Answer:

C. $7.00

Step-by-step explanation:

8 times 7 is 56 + 5 = 61

Find the slope given A(1, -1) B(-2, 1)

Answers

Answer:-2 /3

Step-by-step explanation: 1-(-1)/-2-1

1+1/-3

2/-3

-2/3

Which of the following statements about the image below is true?

Answers

Answer:

d. Line UR and Line VW are parallel

Step-by-step explanation:

If they were to continue going straight, they would not touch, making them parallel.

I hope this helps!

Please answer question 10 and 11 please

Answers

Answer:

d7-dx=(20x|x-3|+40)x  x-3 (|x-3+2)x| x-3|

Step-by-step explanation:

Hope this helps :D

What is the solution to the linear equation?
2.8y + 6 + 0.2y = 5y – 14

Answers

Answer:

y = 10

Step-by-step explanation:

Simplifying

2.8y + 6 + 0.2y = 5y + -14

Reorder the terms:

6 + 2.8y + 0.2y = 5y + -14

Combine like terms: 2.8y + 0.2y = 3y

6 + 3y = 5y + -14

Reorder the terms:

6 + 3y = -14 + 5y

Solving

6 + 3y = -14 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.

6 + 3y + -5y = -14 + 5y + -5y

Combine like terms: 3y + -5y = -2y

6 + -2y = -14 + 5y + -5y

Combine like terms: 5y + -5y = 0

6 + -2y = -14 + 0

6 + -2y = -14

Add '-6' to each side of the equation.

6 + -6 + -2y = -14 + -6

Combine like terms: 6 + -6 = 0

0 + -2y = -14 + -6

-2y = -14 + -6

Combine like terms: -14 + -6 = -20

-2y = -20

Divide each side by '-2'.

y = 10

Simplifying

y = 10

Answer:

y= 11

Step-by-step explanation:

we have:

2.8y + 6 + 0.2y = 5y – 14

or 3y + 6 = 5y -14

and 3y + 6 - 6 = 5y -16 -6

and 3y = 5y -22

and 3y - 5y = -5y +5y -22

so -2y = -22

finally y = -22/-2

or y=11

Hope that useful for you.

What number Could be added in the expression -4 -9 that the value of the expression is 0

Answers

Answer:

+13

Step-by-step explanation:

-4-9 gives -13

when +13 is added to -13 , the expression becomes +13+(-13) =13-13=0

if i’m understanding this correctly -9 + -4 is equal to -13 so wouldn’t you just add 13 to make it 0?

sorry if this is confusing